Regional Vulnerability-Based Disaster Education Strategy: Disaster Mitigation Efforts in Demak Regency, Indonesia - Nur Hamid; Inero Valbuena Ancho; Hanifah Mahat; Dina Ruslanjari; Haning Rofi'ah (LPPM Universitas PGRI Sumatera Barat, 2026)
Disaster mitigation efforts in Indonesia often emphasize structural approaches, while disaster education strategies are frequently implemented without adequate consideration of regional vulnerability variations. This study addresses the problem of the mismatch between disaster education implementation and local vulnerability characteristics in Demak Regency. The study aims to formulate a disaster education strategy based on regional vulnerability data to strengthen community resilience. The analysis focuses on differences in vulnerability levels among sub-districts, the suitability of existing disaster education programs particularly the Satuan Pendidikan Aman Bencana (SPAB) and the mitigation efforts undertaken by the local government. Based on disaster risk reduction theory, community-based disaster education concepts, policy document analysis, and local catastrophe reports, this study uses a descriptive qualitative and quantitative approach, utilizing Z-score analysis to evaluate vulnerability levels across 14 sub-districts. The results show that Karangawen and Mranggen sub-districts are categorized as highly risky locations; however, these spatial risk disparities have not been adequately represented in the implementation of disaster education programs. Additionally, mitigation initiatives are still mostly structural in nature and do not incorporate area-based teaching methods. According to the study's findings, disaster education in Demak Regency has to be more closely matched to the vulnerability profiles of the area. As a novelty, this research demonstrates the importance of integrating quantitative vulnerability data into disaster education planning and practice, offering an evidence-based framework for developing adaptive and sustainable disaster education strategies at the local level.